The evolution of galaxy metallicity scaling relations in cosmological hydrodynamical simulations - de Rossi, Maria Emilia (2015)
The evolution of the metal content of galaxies and its relations to other global properties [such as total stellar mass (M*), circular velocity, star formation rate (SFR), halo mass, etc.] provides important constraints on models of galaxy formation. Here we examine the evolution of metallicity scaling relations of simulated galaxies in the Galaxies-Intergalactic Medium Interaction Calculation suite of cosmological simulations. We make comparisons to observations of the correlation of gas-phase abundances with M* (the mass-metallicity relation, MZR), as well as with both M* and SFR or gas mass fraction (the so-called 3D fundamental metallicity relations, FMRs). The simulated galaxies follow the observed local MZR and FMRs over an order of magnitude in M*, but overpredict the metallicity of massive galaxies (log M* > 10.5), plausibly due to inefficient feedback in this regime. We discuss the origin of the MZR and FMRs in the context of galactic outflows and gas accretion. We examine the evolution of mass-metallicity relations defined using different elements that probe the three enrichment channels (SNII, SNIa, and AGB stars). Relations based on elements produced mainly by SNII evolve weakly, whereas those based on elements produced preferentially in SNIa/AGB exhibit stronger evolution, due to the longer timescales associated with these channels. Finally, we compare the relations of central and satellite galaxies, finding systematically higher metallicities for satellites, as observed. We show this is due to the removal of the metal poor gas reservoir that normally surrounds galaxies and acts to dilute their gas-phase metallicity (via cooling/accretion onto the disk), but is lost due to ram pressure stripping for satellites.